Clinical correlates of the restless legs syndrome - Luis Fabiano Marin; Andre Carvalho Felicio; William Adolfo Santos; Lucila Bizari Prado; Gilmar Fernandes Prado (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To determine the clinical correlates of the restless legs syndrome (RLS) in a Brazilian sleep disorders center. METHODS: We retrospectively studied 118 patients with RLS from January, 2004, to December, 2010. The analyzed variables were: age at disease onset, gender, race, years of school instruction, primary and secondary RLS, and treatment options. RESULTS: Among the studied patients, 83.9% were women with a female/male sex ratio of 5:1. Mean age of the patients at symptom onset ± standard deviation was 41.7±17.9 years-old. The primary RLS was found in 85% of patients. The other 15% remainders consisted of secondary forms, and they were associated with neuropathy, iron deficiency anemia, end-stage renal disease, or Parkinson's disease. Drug therapy for RLS was introduced in 67% of patients. CONCLUSIONS: Most patients presented primary RLS with an early disease onset. Further epidemiological studies are welcomed to provide better information on secondary RLS in Brazil.